Sticky Power Global Financial Networks in the World Economy - Haberly, Daniel (Oxford University Press, 2022)
Modern civilization revolves around money. However, money is a paradox. It is nothing more than a representation of and medium for decentralized networks of social trust, but its production is controlled by highly centralized networks of firms, places, and governments, and there is never enough of it to go around. Moreover, given that the creation of money, as credit, is based on expectations, money is at its heart an instrument for human agency to change the future. At the same time, however, the financial systems that produce money are deeply rooted in the past, and perpetuate themselves through history. This book seeks to deepen our understanding of the paradox of money, by introducing a novel conceptual lens-that of Global Financial Networks-to cast new light on the geography, history, politics, and sociology of finance from the middle ages to the global financial crisis and beyond. It shows that the power of finance is inherently "sticky"; with what are generally assumed to be new innovations such as "offshore" finance actually dating back centuries, and the architecture of global financial networks more broadly adapting to the rise and fall of empires and new technologies while changing surprisingly little in their basic character; or at most changing very slowly. A recognition of the mechanics of this durability, it is argued, calls for a new approach to reforming finance which is less reactively focused on regulation, and more proactively focused on building new institutional systems with a long-term "sticky power" of their own.